(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
This work focuses on shielding buried high-voltage (HV) cables, examining two possible screen topologies (open and closed) and various materials (conductive and ferromagnetic). In a closed Shield, the shield surrounds the cables.